DEVELOPMENT OF UNO CARD FOR TEACHING VOCABULARY AT JUNIOR HIGH SCHOOL STUDENTS - Fitri, Devi Zulia; Widiarini, Widiarini; Saifudin, Ahmad (PROJECT (Professional Journal of English Education), 2024)
This study aims to how Uno cards can be used to enhance the vocabulary of seventh-grade students in understanding descriptive texts, focusing on both the development process and the outcomes achieved. Vocabulary is very important because it serves as the cornerstone of English language skills. Based on the findings of interviews, questionnaires and observations, there are still very many grade VII students who have difficulty in understanding English vocabulary. Researchers use the ADDIE R&D model in Raiser and Mollenda, researchers use 5 steps of ADDIE, namely: analysis, Product Design, development, implementation, evaluation. The difference with the previous researcher is the subject, material and purpose of the research. Validation provides the researcher with a score. The instrument gets a score of 85%, which signifies "valid", Media expert validation Receiving scores 82,5%, indicating "valid", and the validation of the subject matter expert Receiving scores 88,89%, means "very valid". Furthermore, based on the students' reactions to the media, they received an 88,22%, indicating "very valid".